find a formula for the inverse of the function:
f(x) = (4x-1)/(2x+3)
i substituted f(x) for x and tried solving, and i ended up with (3x+1)/2, but that doesnt check
any help would be appreciated..
so you want to solve $\displaystyle x = \frac {4y - 1}{2y + 3}$ for $\displaystyle y$
$\displaystyle \Rightarrow x(2y + 3) = 4y - 1$ .........multiplied both sides by $\displaystyle 2y + 3$
$\displaystyle \Rightarrow 2xy + 3x = 4y - 1$ ..........expanded the brackets on the left
$\displaystyle \Rightarrow 4y - 2xy = 3x + 1$ ..........added $\displaystyle 1 - 2xy$ on both sides
$\displaystyle \Rightarrow y(4 - 2x) = 3x + 1$ .........factored out $\displaystyle y$ from the left hand side
$\displaystyle \Rightarrow y = \frac {3x + 1}{4 - 2x}$
and that's your inverse function
EDIT: Ah, I didn't see that you responded, galactus. But i'll leave what i did up since i used a different method